Educação do campo e ensaios da escola do trabalho: a materialização do trabalho como princípio educativo na escola itinerante do MST Paraná - Leite, Valter de Jesus (2017)
This work has the political struggle as background and guidance inspiration, it aims to reflect the ways in which the school can be a place of humanisation, by putting the concept of work as key to build up a human being and acknowledging the human being as carrier of human richness – science, art, philosophy. The work pursues to understand how the “Itinerant School” of Parana (state of Brazil), rooted into the struggle for land reform, materialises the relation between work, education and school education foreseeing the holistic human formation of the students. To pursue this objective this research draws on the documentary analysis, bibliographical review and field visits, using field journal. The introduction initially presents, in summary, the central issues on the relations of production in the rural areas of Brazil. This is understood within the capitalist mode of production, which determines the social relations of production and modes of life’s organisation. Within this context, there is a brief historical review of the MST (Landless Movement) and the journey that leads this movement to understand the need to place education and school education in its political agenda. This will also influences the birth of the Itinerant School in the State of Paraná. It is evidenced the challenges to link the struggle for access to formal education with the struggle against the political tutelage of the State, when it was decided to have the School at the camping site. It is characterised the historical journey of the twelve active itinerant schools in the state of Parana, their objectives remained to pursue to build a new status regarding the link between content and format rooted in the Socialist Pedagogy and in the deep expertise of the Movement Pedagogy. The second chapter presents data on the conceptual and categorial universe on the relation of work and education, based on the fathers of the materialistic dialectical historical method, Marx and Engels. The historical construction of the Socialist and Marxist pedagogies is the subject of the third chapter, as an overview of the built possibilities in the history of education and of the educational thinking to pursue an effective link between work – as human and humanising action – and education. The socialist pedagogy, the unique school of work, the unitarian school, the historical-critical pedagogy and the MST’s pedagogy are identified in which is central to this work. From a survey “in loco” and accompaniment groups as a subject belonging to the Educational Branch of MST, it is presented an analysis of the construction of theoretical, political and methodological choices of the history of the Itinerant School, analysing the case of the Parana’s schools. It is presented the conceptual and analytical elements, as well as, the experiences founded currently in the state of Parana out of the construction of a school proposal anchored in the generative themes of the Freire’s tradition and incorporated into the challenge based on the Complexes of Pistrak’s Studies. It is identified the connexion of the Itinerant School with the Socialist pedagogy by updating the sense of School of Work, and by pursuing the relation between work and school, having the labour as key category that enables the unitarian apprehension of the logic that supports the contradiction between the capital and the work (current times). As a result of this process, it engages the work as a mean of education by the insertion into collective processes of self-service, work socially necessary, of struggle, cultural and study expression that develops, for the new generations, traces of a socialist and multilateral developed personality. By organising collectively the school community claims the right conditions to build and qualify the struggle for human richness development, linked to the Landless Movement’s strategies, in the process of building up the Popular Land Reform. It is considered the current experiences with the Itinerant School in Parana, even taking into account its limitations and tensions coming from the relationship with the State and absence of structural conditions to embed this kind of complex school programme, it amplifies the meaning of being a school belonging to the working class, especialy in the middle of the land occupation. As the categories of educative work acquire a new articulation in the Complex of Studies in a more organised mode, it ensures and reallocates strongly, not without limitations, the work with the foundation of sciences, art, culture and technologies developed by human beings during the course of history, in connexion with agro-ecology, social struggles and self-organization. It configures as seeds of the socialist education in present times, in the formation of strugglers and builders of a new society.